Outrun the moon - Lee, Stacey (Stacey Heather) (G. P. Putnam's Sons, 2016)
Fifteen-year-old Mercy Wong is determined to break from poverty in Chinatown, and she gains admittance to a prestigious finishing school through a mix of cunning and bribery. She soon discovers that getting in was the easiest part, and must carve a niche among the spoiled heiresses. When the earthquake strikes on April 18, Mercy and her classmates are forced to a survivor encampment, but her quick-witted leadership rallies them to help in the tragedy's aftermath.